The role of cytogenetics and molecular biology in the diagnosis, treatment and monitoring of patients with chronic myeloid leukemia - Luiza Emy Dorfman; Maiara A. Floriani; Tyana Mara R. D. R. Oliveira; Bibiana Cunegatto; Rafael Fabiano M. Rosa; Paulo Ricardo G. Zen (Sociedade Brasileira de Patologia Clínica, 2018)
ABSTRACT Chronic myeloid leukemia (CML) is the most common myeloproliferative disorder among chronic neoplasms. The history of this disease joins with the development of cytogenetic analysis techniques in human. CML was the first cancer to be associated with a recurrent chromosomal alteration, a reciprocal translocation between the long arms of chromosomes 9 and 22 - Philadelphia chromosome. This work is an updated review on CML, which highlights the importance of cytogenetics analysis in the continuous monitoring and therapeutic orientation of this disease. The search for scientific articles was carried out in the PubMed electronic database, using the descriptors "leukemia", "chronic myeloid leukemia", "treatment", "diagnosis", "karyotype" and "cytogenetics". Specialized books and websites were also included. Detailed cytogenetic and molecular monitoring can assist in choosing the most effective drug for each patient, optimizing the treatment. Cytogenetics plays a key role in the detection of chromosomal abnormalities associated with malignancies, as well as the characterization of new alterations that allow more research and increase knowledge about the genetic aspects of these diseases. The development of new drugs, through the understanding of the molecular mechanisms involved, will allow a possible improvement in the survival of these patients.